2009
DOI: 10.1021/jp9015504
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Zinc Antimonate Nanoisland Attachment and Morphology Control of ZnO Nanobelts by Sb Doping

Abstract: Hierarchical heterostructures of zinc antimonate nanoislands on ZnO nanobelts were prepared by simple annealing of the polymeric precursor. Sb can promote the growth of ZnO nanobelts along the [552] direction because of the segregation of Sb dopants on the +(001) and (110) surfaces of ZnO nanobelts. Furthermore, the ordered nanoislands of toothlike ZnSb2O6 along the [001]ZnO direction and rodlike Zn7Sb2O12 along the [110]ZnO direction can be formed because of the match relation of the lattice and polar charges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The doping of the Sb element is responsible for the formation of the zigzag surface in ZnO microwires, which is in accordance with the literature. 18,36 To determine the composition of Sb in ZnO microwires, we performed the EDX analysis, which showed that the Sb concentration was 0.3% within the measurement limit of EDX. The zigzag rough surface is even along the whole microwire, which implies the uniform Sb doping in ZnO.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…The doping of the Sb element is responsible for the formation of the zigzag surface in ZnO microwires, which is in accordance with the literature. 18,36 To determine the composition of Sb in ZnO microwires, we performed the EDX analysis, which showed that the Sb concentration was 0.3% within the measurement limit of EDX. The zigzag rough surface is even along the whole microwire, which implies the uniform Sb doping in ZnO.…”
Section: Structural and Optical Propertiesmentioning
confidence: 99%
“…Nano-heterostructures exhibit unique properties and multiple functions which cannot be realized in singlecomponent materials and they have been attracting increasing research interest recently. [31][32][33][34][35][36][37] Core/shell radial heterojunction NWs are superior to bulk heterojunction devices since the carrier separation takes place in the radial direction, with a carrier collection distance that is smaller or comparable to the minority carrier diffusion length. 22,38 Herein, photodetectors were fabricated based on Ohmic contacted individual Zn 2 SnO 4 -sheathed ZnO radial heterostructured NWs.…”
Section: Introductionmentioning
confidence: 99%
“… 25 The solutes prefer to segregate from the host and occupy the surface of the nanostructures, result in a decreased surface energy. 26 Hence we propose that Sb is responsible for the zigzag surface and zigzag shaped microwires are surrounded by (0002), (0110) and (2110) as the surface. 27 …”
Section: Resultsmentioning
confidence: 94%
“…Some researchers reported that Sb in ZnO have an effect on the morphology of nanostructure. [25][26][27] The introduction of Sb can alter the morphology of the ZnO nanomaterials, including crystal size, orientation, and aspect ratio, which also have important effects on their electrical and optical properties, gas sensitivity and catalytic properties. 28 When Sb was introduced into ZnO, it has higher resistance and diffuse reectivity than those of the undoped ZnO.…”
Section: Introductionmentioning
confidence: 99%